Punitive Pregnancy: Pregnancy and Labor as Female Punishment in the Sayings of the Desert Fathers - Buckner, Candace (Journal of the American Academy of Religion, 2025)
In recent years, popular news articles have drawn attention to the condition of incarcerated pregnant women in the United States. They have highlighted how substandard prenatal and parturition care has resulted in poor maternal outcomes and alleged that these consequences coincide with an increased tendency to view difficult pregnancy and labor as a valid part of the penal experience. However, the notion that pregnancy and difficult labor serve as punishment did not originate in the modern era; early Christian literature provides multiple examples of pregnancy and difficult labor as punishment. Specifically, anecdotes in the Apophthegmata Patrum or Sayings of the Desert Fathers detail women whose transgressions are punished with pregnancy or painful labor. I argue that these stories merge ancient understandings of the female body as slated for suffering, especially in childbirth, and penal discourses that favor punishment as written on the body to imagine pregnancy and difficult labor as punitive.